Work of Incident Management Teams in the Laboratory: Measuring C2 Performance under Experimental Conditions - Romeijn, Lars; Landsberg, Lennart Walter; Mudimu, Ompe Aimé (Proceedings of the International ISCRAM Conference, 2026)
Past incident events clearly demonstrate the relevance of effective command and control (C2) work. In particular, situation reconnaissance and visualization, as the foundation of decision-making processes, may potentially be optimized through new technological capabilities. To examine assumptions through automated position visualizations, an experimental study was designed to observe work of Incident Management Teams (IMTs) under laboratory-like conditions. For this purpose, a newly synthesized approach combining established situation awareness measurement methodologies was applied. Through three iterations of the experiment with different IMTs, initial measurement results were obtained and analyzed. When automated position visualizations was utilized, more accurate localization and a higher level of agreement within teams regarding location assessments were observed. In addition, an improved comprehension of the situation was identified. By correlation analyses with applied measurement methods of incident management performance, the reciprocal relationship between C2 performance and situation awareness can be examined, thereby allowing for an assessment of the effects of such information media.